2022
DOI: 10.1080/14763141.2022.2094825
|View full text |Cite
|
Sign up to set email alerts
|

Examination of running pattern consistency across speeds

Abstract: Duty factor (DF) and step frequency (SF) are key running pattern determinants. However, running patterns may change with speed if DF and SF changes are inconsistent across speeds. We examined whether the relative positioning of runners was consistent: 1) across ve running speeds (10-18 km/h) for four temporal variables [DF, SF, and their subcomponents: contact (t c ) and ight (t c ) time]; and 2) across these four temporal variables at these ve speeds. Threedimensional whole-body kinematics were acquired from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…In relation to SF, this variable can reveal individual strategies to increase running speed ( Dorn et al, 2012 ) or achieve top-end running speeds ( Salo et al, 2011 ). Indeed, the consistency in SF was shown to decrease as speed differences increased (tested running speeds: 10–18 km/h) ( Patoz et al, 2022 ) and each runner was shown to self-optimize his step length over SF ratio ( Hunter et al, 2017 ; van Oeveren et al, 2021 ). Even in subgroups of individuals with similar sprint velocities, a range of SF and step length combinations are present ( Hunter et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to SF, this variable can reveal individual strategies to increase running speed ( Dorn et al, 2012 ) or achieve top-end running speeds ( Salo et al, 2011 ). Indeed, the consistency in SF was shown to decrease as speed differences increased (tested running speeds: 10–18 km/h) ( Patoz et al, 2022 ) and each runner was shown to self-optimize his step length over SF ratio ( Hunter et al, 2017 ; van Oeveren et al, 2021 ). Even in subgroups of individuals with similar sprint velocities, a range of SF and step length combinations are present ( Hunter et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of proper training techniques in hurdles must pay attention to speed and strength techniques. One application of strength training has been used by (Patoz et al, 2023) namely the use of dynamic body weight training. For this exercise is widely used by top athletic trainers in the world but the constraints on this exercise have not been scientifically proven in increasing speed.…”
Section: Introductionmentioning
confidence: 99%
“…Given that runners were injured at the time of testing in most studies assessing the association between biomechanics and AT, these findings of potential kinematic and GRF variables related to AT may primarily reflect postinjury compensations and not potential risk factors associated with developing AT. In addition, there were noted differences in testing conditions across these studies, such as running speed, which is known to have an effect on both running mechanics (15,16) and Achilles tendon peak forces and loading rates (17) and may contribute to the inconsistent findings. Given the limited prospective research assessing biomechanical differences between runners who do and do not go on to develop an AT, the aims of this study were 1) to prospectively identify preinjury running biomechanics that differ between collegiate runners who did and did not go on to develop AT and 2) determine if preinjury between-limb asymmetry in running biomechanics is associated with sustaining an AT.…”
mentioning
confidence: 99%